ODOO-BASED STOCK MANAGEMENT SYSTEM DESIGN AT PT. IMEDIA NUSANTARA - Nurhasana, Renu (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
Designing an efficient and effective stock management system is an important challenge for companies in optimizing their supply chain operations, namely PT. Imedia Nusantara, a fast grow retail company, faces the same challenges in managing their stock. In order to increase the efficiency of stock management and reduce inventory discrepancies, this study aims to design and implement an Odoo-based stock management system at PT. Imedia Nusantara. The method used in this research is Rapid Application Development (RAD), which is suitable for this research because it can support Enterprise Resource Planning (ERP) systems. This research involved several stages, including requirements planning, in which the authors conducted an analysis of the needs needed to support the inventory process at PT. Imedia Nusantara. Furthermore, in the design stage (design workshop), the authors use the unified Modeling Language (UML) modeling to design the system. At the implementation stage, the author applies the existing system at PT. Imedia Nusantara, and conduct testing after the implementation stage. The result of this study is the implementation of an ERP system using the Odoo application version 16 with the Inventory module to record stock items.